Mobile stroke unit triage of patients with a suspected stroke: a novel solution to reducing suspected stroke admissions in busy emergency departments. Issue 2 (6th February 2018) - Shuaib, Ashfaq; Amlani, Shy; Kalashyan, Hayrapet; Morrison, Laurel; Khan, Khurshid; Jickling, Glen; Buck, Brian; Butcher, Kenneth; Saqqur, Maher; Jeerakathil, Thomas
Abstract : Background: Evaluation of patients with a suspected stroke is one of the most common neurological emergencies requiring rapid, comprehensive assessment by the stroke service to determine patient eligibility for timely reperfusion therapies. Prehospital evaluation may help to improve patient selection and reduce avoidable admissions to overcapacity emergency departments. Methods and results: We report on our early experience of prehospital triage of patients with a suspected stroke using a mobile stroke unit (MSU) equipped with CT scanner in rural Alberta. During the initial 4 months of operation, 28 patients were evaluated by the team in the MSU. Eight patients were within the time window of thrombolysis and were treated with intravenous tissue plasminogen activator in the MSU. No patients suffered haemorrhage or any other complications. Fourteen patients with multiple aetiologies (stroke mimics 6, transient ischaemic attacks 2, subacute stroke outside thrombolysis window 2, intracranial haemorrhage 3 and cerebral contusion 1) were assessed in the field and transferred to the tertiary hospital. Six patients after assessment and imaging were repatriated back to the local hospital as they were deemed stroke mimics or were outside of the reperfusion window. Conclusions: The MSU offers a novel approach to performing timely evaluation and treatment of patients with a suspected stroke in rural settings and may help reduce admissions to overcapacity tertiary care facilities.